(untitled) (Al-Academy, 2023)
Technological development has had a major impact on the theatrical art in building and establishing visual presentation and employing modern technologies as one of the elements of expression, which prompted theater workers to respond to this development on the audio-visual level, creating new horizons for directors and discovering possibilities that they employed according to new visions that relied on experimentation and innovation. And freedom from the prevailing and traditional, and perhaps the use of digital computers has achieved remarkable success in embodying the formal model, controlling the movement of the actors, and the possibility of changing the scenery, as it completes the image to enter the stage of construction and effectiveness and carrying multiple connotations, which created a dialectic between the artistic and the technical in the formal construction. The research included an introduction chapter. To introduce the problem and the importance of research, then the theoretical establishment consists of two sections: the first section (the concept of the artistic and the technical), the second section (the dialectics of the technical and the artistic in formal construction). Then the methodological procedures were carried out, which consisted of analyzing the research sample, showing the play (The Café) and performing a play (Red Carpet), and after the analysis came up with a set of results, including:Despite the services provided by modern technology and finding alternatives to problems in theatrical performances, in some performances it marginalizes the role of the actor, which is an essential and indispensable element.Technology has become dominant in theatrical performances and has created a break with traditional doctrines, and there was an overwhelming desire on the part of the director and designer to use it to the point of exaggeration, which led to an adverse reaction among the recipients. Then he concluded this research with a list of sources and references and a summary of the research in English